Innovation of Moringa Leaf Products to Attract the Interest of the Younger Generation at Rumah Kelor Anjani, West Java - Shiva Naura Haydia Yusan; Nadzala Salsabila Azahra; Melisa Zesik; Yeni Seftiani; Itto Turyadi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine product innovations involving processed moringa leaves developed by Micro, Small, and Medium Enterprises (MSMEs) at Rumah Kelor Anjani and to assess the role of these innovations in increasing consumer interest, particularly among the younger generation. A qualitative, descriptive approach was used to conduct this study. Data collection was conducted through in-depth online interviews with entrepreneurs who have been running their businesses since 2015. The research findings indicate that moringa leaves hold significant potential as a functional food ingredient; however, their use remains hindered by negative public perceptions and low levels of awareness. Product innovations, such as the development of moringa-based food and beverage products, the selection of more modern packaging, and adaptation to the consumption trends of the younger generation, have proven successful in increasing product appeal. Additionally, marketing strategies via social media are considered effective for reaching young consumers. Thus, product innovations targeting the preferences of the younger generation and public education are crucial for increasing the acceptance of moringa leaf-based products.